REACTION KINETICS OF Cu ELECTRO-DEPOSITION ON THE SURFACE OF TiO2/GRAPHITE - Rahmawati, Fitria; Mawasthi, Wanodya Anggit; -, Patiha (Jurnal Riset Kimia, 2015)
Research on the kinetics of electrode reaction during copper electro-deposition on the surface of TiO2/graphite has been conducted. The aims of this research are to determine the ratio of anodic reaction rate to cathodic reaction rate , the ratio of anodic rate constant to cathodic rate constant , the equilibrium constant when the reaction reach equilibrium condition and to study the polarization in the electro-deposition reaction. Copper was deposited electrochemically from CuSO4 solution at various concentration i.e. 0.1 M; 0.2 M; 0.3 M; 0.4 M; 0.5 M. In every 5 minutes during electro-deposition process, the pH changes in anode cell was recorded and the change of Cu2+ concentration was also analyzed by spectrophotometric method. The result shows that the reaction order of Cu2+ reduction is first order and the oxidation of H2O in anodic cell is zero order. The ratio of anodic rate constant to cathodic rate constant, is 4.589´10-3 ± 0.071´10‑3. It indicates that the reaction rate  in cathode is larger than the reaction rate in anode and it allowed polarization.  The electrochemical cell reached equilibrium after 25 minutes with the equilibrium constant is 8.188´10-10 ± 1.628´10-10.